Biodegradation of diisobutyl phthalate using fungi plastisphere isolated from plastic waste in mangrove Kadilangu area - Baharudin, Jalu Bahtiar; Rakhmawati, Anna (Jurnal Natural, 2025)
Diisobutyl phthalate, an additive in plastic production belonging to the group of xenobiotic substances, has a negative impact on human health, especially on the reproductive system. In Indonesia, the presence of plastisphere fungi is often used as a degrading agent for xenobiotic substances. Plastisphere fungi show enzymatic activity to degrade xenobiotic substances but have not been widely studied. Therefore, this research aims to assess the ability of several genera of plastisphere fungi to degrade diisobutyl phthalate and evaluate their enzyme activity and their tolerance under heavy metal stress. The method for determining degradation used an UV-VIS spectrophotometer at wavelength of 362 nm, fungal identification used profile matching method, the presence of oxidoreductase enzymes in fungi was assessed using qualitative method with selective media (ABTS 200 mg/L, phenol red 50 mg/L, and methylene blue 4%), and their tolerance to heavy metals at a concentration of 50 ppm was analyzed using tolerance index method. The identification results of fungi come from the genera Acremonium and Aspergillus, and tolerance index analysis revealed that these genera have high tolerance to very tolerant (0.91-1.23) to the metals (copper, chromium, and lead) induced stress. Evaluation of oxidoreductase enzyme activity showed that Aspergillus from isolate LT2(1) had laccase, lignin peroxidase, and manganese peroxidase enzymes. Analysis of diisobutyl phthalate degradation using an UV-VIS spectrophotometer with wavelength of 362 nm showed that all isolates were able to degrade diisobutyl phthalate within 14 days of incubation period at room temperature (20oC-23oC) under copper-induced stress, with the highest isolate degrading diisobutyl phthalate is Aspergillus LT2(1) (75.57%), followed by Acremonium PK2(2) (60.65%), and Aspergillus HT3(2) (36.79%). Based on these findings, it can be concluded that Aspergillus LT2(1) shows the best agent to degrade diisobutyl phthalate because it has the ability to regulate the flow of nutrients and energy through the structure of hyphae and mycelial tissues and produces oxidoreductase enzymes that are able to degrade recalcitrant compounds.